Schools of Management, Islamic Management and Science - Fontaine, Ridhwan (International Journal of Economics, Management and Accounting, 2023)
This study starts with an ethical dilemma. A Muslim business leader wants to respect the spirit and the letter of Islamic law on the one hand. On the other hand, he wants to maximize profits as profit maximization is the cornerstone of modern management. This study reviews the ideas of great thinker, the history of management, and the rise of multiple schools of management. At the same time, the rate of organizational failure is extremely high. A Foucault-type analysis shows how virtually all of the discourse on management is controlled by American scholars. This discourse depends a lot on “numbers”, yet these numbers turn out to be quite subjective. Popper’s analysis of the social sciences is then explored. The conclusion is that management theories can be best described as “useful myths.” The dilemma for the Muslim business leader disappears.